Reforming Pre-Marital Agreements In Indonesian Muslim Family Law: Between Legal Legitimacy And Cultural Resistance - Kalamiah, Moh. Jeweherul; Khoir, Ikmalul; Baharuddin, Ahmad Syukran (Hukum Islam, 2025)
The reform of prenuptial agreements in Indonesian Islamic family law reveals ongoing tensions between formal legal legitimacy and deep-rooted cultural resistance within society. Using a socio-legal qualitative approach within a normative-critical framework, this study combines analysis of legislation, classical Islamic jurisprudence, and in-depth interviews with religious leaders and Muslim couples in Islamic boarding school communities in East Java. The findings show that community rejection of prenuptial agreements is influenced more by cultural narratives, low legal awareness, and institutional weaknesses than by theological objections in Islamic law. The novelty of this article lies in the development of an integrative analytical framework that combines maqāṣid al-sharī‘ah with socio-legal theories of legal culture and legal awareness to explain the operational failure of Islamic legal instruments that are normatively valid in social practice. Unlike previous studies that tend to separate normative and sociological analysis, this article bridges Islamic legal reasoning with the everyday legal experiences of Muslim communities to identify structural, cultural, and administrative obstacles simultaneously. This study further offers three main reform strategies, namely regulatory simplification, contextual Islamic legal education, and institutional integration, in order to reposition prenuptial agreements as adaptive legal instruments for the protection of rights, the prevention of structural gender inequality, and the strengthening of justice in Islamic family law. Comparisons with practices in Malaysia and Morocco confirm that prenuptial agreements are consistent with Sharia principles when supported by systemic legal and institutional adaptations.